Formation of professionally oriented lexical competence among students of non-linguistic universities in the training program «Technosphere Safety»: a case study of the English language course - E. N. Bazalina (Вестник Майкопского государственного технологического университета, 2024)
Modern methods of teaching foreign languages in non-linguistic universities are determined by the need to effectively combine language and professional training that meets the requirements of the Federal State Educational Standard of Higher Education (FSES HE). The key goal of this system is to develop students’ skills in understanding professionally-oriented information and developing the competence to communicate in a foreign language in professional situations.The article discusses issues related to the formation of professionally oriented lexical competence among students of the Federal State Budgetary Educational Institution of Higher Education «Maikop State Technological University» in the training program «Technosphere Safety». The study emphasizes the relevance of the topic, since when studying a professional foreign language it is impossible to develop lexical competence without the ability to work with thesaurus in one’s professional ﬁeld.The goal of the research is to clarify the methods of developing professionally-oriented lexical competence among students of non-linguistic universities in the training program 20.03.01 «Technosphere Safety» in the process of reading texts in the specialty in English. The extent to which it is necessary to select lexical material and compile an individual thesaurus with a professional focus is assessed, which allows students to better understand professional texts, expand their vocabulary and accurately use professional terminology.Professionally oriented texts were the research material; linguistic and lexical units were analyzed, the skill of developing lexical competence among students was practiced.The research is based on complex research methods, consisting of theoretical methods (deductive analysis, method of statistical work with lexical material, comparative analysis) and empirical methods (observation method and data analysis).As a result of the research, a strategy for working on vocabulary when reading professionally oriented texts has been proposed, and the most effective exercises for developing lexical competence among students in the training program «Technosphere Safety» have been identiﬁed.Key conclusions: the formation of professionally oriented lexical competence among students of non-linguistic universities when working with foreign language texts on the topic «Technosphere Security» helps to analyze the information received and to form lexical competence and the skill of using an individual terminological thesaurus in the professional ﬁeld, expanding the vocabulary in the specialty.